Tuberculosis drug streptomycin as a potential cancer therapeutic: inhibition of miR-21 function by directly targeting its precursor - Bose, Debojit; Jayaraj, Gopal Gunanathan; Suryawanshi, Hemant; Agarwala, Prachi; Pore, Subrata Kumar; Banerjee, Rajkumar; Maiti, Souvik (Angewandte Chemie-International Edition, 2012)
Keywords: Apoptosis; drug discovery; Gene expression; inhibitors; RNA

Thermodynamics and solvation dynamics of BIV TAR RNA-Tat peptide interaction - Goel, Teena; Kumar, Santosh; Maiti, Souvik (Molecular Biosystems, 2013)
The interaction of the trans-activation responsive (TAR) region of bovine immunodeficiency virus (BIV) RNA with the Tat peptide is known to play important role in viral replication. Despite being thoroughly studied through a structural point of view, the nature of binding between BIV TAR RNA and the BIV Tat peptide requires information related to its thermodynamics and the nature of hydration around the TAR-Tat complex. In this context, we carried out the thermodynamic study of binding of the Tat peptide to the BIV TAR RNA hairpin through different calorimetric and spectroscopic measurements. Fluorescence titration of 2-aminopurine tagged BIV TAR RNA with the Tat peptide gives their binding affinity. The isothermal titration calorimetric experiment reveals the enthalpy of binding between BIV TAR RNA and the Tat peptide to be largely exothermic with the value of -11.7 (SEM 0.2) kcal mol(-1). Solvation dynamics measurements of BIV TAR RNA having 2-AP located at the bulge region have been carried out in the absence and presence of the BIV Tat peptide using the time correlated single photon counting technique. The solvent cage around the Tat binding site of RNA appears to be more rigid in the presence of the Tat peptide as compared to the free RNA. The displacement of solvent and ions on RNA due to peptide binding influences the entropic contributions to the total binding energy.

Tale of RNA G-quadruplex - Agarwala, Prachi; Pandey, Satyaprakash; Maiti, Souvik (Organic & Biomolecular Chemistry, 2015)
G-quadruplexes are non-canonical secondary structures found in guanine rich regions of DNA and RNA. Reports have indicated the wide occurrence of RNA G-quadruplexes across the transcriptome in various regions of mRNAs and non-coding RNAs. RNA G-quadruplexes have been implicated in playing an important role in translational regulation, mRNA processing events and maintenance of chromosomal end integrity. In this review, we summarize the structural and functional aspects of RNA G-quadruplexes with emphasis on recent progress to understand the protein/trans factors binding these motifs. With the revelation of the importance of these secondary structures as regulatory modules in biology, we have also evaluated the various advancements towards targeting these structures and the challenges associated with them. Apart from this, numerous potential applications of this secondary motif have also been discussed.

Terminal uridylyl transferase mediated site-directed access to clickable chromatin employing CRISPR-dCas9 - George, Jerrin Thomas; Azhar, Mohd; Aich, Meghali; Sinha, Dipanjali; Ambi, Uddhav B.; Maiti, Souvik; Chakraborty, Debojyoti; Srivatsan, Seergazhi G. (Journal of the American Chemical Society, 2020)
Locus-specific interrogation of target genes employing functional probes such as proteins and small molecules is paramount in decoding the molecular basis of gene function and designing tools to modulate its downstream effects. In this context, CRISPR-based gene editing and targeting technologies have proved tremendously useful, as they can be programmed to target any gene of interest by simply changing the sequence of the single guide RNA (sgRNA). Although these technologies are widely utilized in recruiting genetically encoded functional proteins, display of small molecules using CRISPR system is not well developed due to the lack of adequate techniques. Here, we have devised an innovative technology called sgRNA-Click (sgR-CLK) that harnesses the power of bioorthogonal click chemistry for remodeling guide RNA to display synthetic molecules on target genes. sgR-CLK employs a novel posttranscriptional chemoenzymatic labeling platform wherein a terminal uridylyl transferase (TUTase) was repurposed to generate clickable sgRNA of choice by site-specific tailoring of multiple azide-modified nucleotide analogues at the 3' end. The presence of a minimally invasive azide handle assured that the sgRNAs are indeed functional. Notably, an azide-tailed sgRNA targeting the telomeric repeat served as a Trojan horse on the CRISPR-dCas9 system to guide synthetic tags (biotin) site-specifically on chromatin employing copper-catalyzed or strain-promoted click reactions. Taken together, sgR-CLK presents a significant advancement on the utility of bioorthogonal chemistry, TUTase, and the CRISPR toolbox, which could offer a simplified solution for site-directed display of small molecule probes and diagnostic tools on target genes.